Effect of hindlimb unweighting on expression of hypoxia-inducible factor-1? vascular endothelial growth factor, angiopoietin, and their receptors in mouse skeletal muscle - Wagatsuma, A (Physiological research, 2008)
Hindlimb unweighting (HU) leads to capillary regression in skeletal muscle. However, the molecular mechanism(s) remains to be elucidated. To gain insight into the regulation of this process, we investigated gene expression of hypoxia-inducible factor-1? (HIF-1?), vascular endothelial growth factor (VEGF), angiopoietin, and their receptors in the atrophied muscle induced by HU. The hindlimbs of mice were unweighted by tailsuspension and then the gastrocnemius muscles were isolated after 10 days. To assess the capillary distribution, the capillary endothelium in frozen transverse sections was identified by staining for alkaline phosphatase. The mRNA levels were analyzed using a real-time reverse transcription-polymerase chain reaction. After 10 days of HU, the number of capillaries around a muscle fiber was significantly decreased by 19.5 %, suggesting that capillary regression appears to occur. The expression of HIF- 1? was significantly down-regulated after 10 days of HU. The expression of VEGF remained unchanged, whereas those of Flt-1, KDR/Flk-1, and neuropilin-1 were significantly down-regulated, suggesting that VEGF signaling through these receptors would be attenuated. The expression of angiopoietin-1, and -2, as well as their receptor, Tie-2 were also significantly down-regulated, suggesting that angiopoietin-1 signaling through Tie-2 would be attenuated. These findings suggest that alterations in expression of VEGF, angiopoietins, and their receptors may be associated with capillary regression after HU.
Keywords: angiopoetin-2; Vascular Endothelial Growth Factor A; kapiláry; Receptors, Vascular Endothelial Growth Factor; Reverse Transcriptase Polymerase Chain Reaction; Angiogenic factor; zvířata; Receptors, Cell Surface; zadní končetina - imobilizace; receptory vaskulárního endoteliálního růstového faktoru; Hypoxia-Inducible Factor 1, alpha Subunit; Animals; faktor 1 indukovatelný hypoxií - podjednotka alfa; vaskulární endoteliální růstový faktor A; angiopoetin-1; Muscle, Skeletal; Muscle atrophy; Female; Angiopoietin-1; Mice; Angiopoietin-2; Histocytochemistry; kosterní svaly; financování organizované; receptory buněčného povrchu; polymerázová řetězová reakce s reverzní transkripcí; ženské pohlaví; Hindlimb unweighting; Capillary regression; RNA; myši; komplementární DNA; Hindlimb Suspension; Financing, Organized; Capillaries; DNA, Complementary; histocytochemie